Exercise as a treatment for sarcopenia: an umbrella review of systematic review evidence. Issue Volume 107:Issue (2020) (June 2020) - Moore, Sarah A.; Hrisos, Nina; Errington, Linda; Rochester, Lynn; Rodgers, Helen; Witham, Miles; Sayer, Avan A.
Abstract: Background: Sarcopenia is a progressive and generalised skeletal muscle disorder, and a powerful predictor of adverse health outcomes. Exercise is a widely recommended treatment but consensus about the best approach is lacking. Objective: To synthesise current systematic review evidence on the effectiveness of exercise in the treatment of sarcopenia to inform clinical practice. Data sources: Five electronic databases were searched (15 November 2018): Cochrane Database of Systematic Reviews; MEDLINE without revisions; EMBASE; Scopus; and Web of Science. Study selection or eligibility criteria: Systematic reviews and meta-analyses of randomised controlled trials evaluating exercise to treat sarcopenia in adults including sarcopenic outcomes. Study appraisal and synthesis methods: Review data were extracted and quality assessed (using the AMSTAR 2) by two independent assessors. Due to a lack of eligible reviews, a narrative synthesis of the evidence was performed. Results: Two reviews were identified which included seven studies with 619 participants. Study exercise interventions included: resistance; mixed and whole body vibration training programmes. Review findings demonstrate limited low quality evidence of positive effects of mixed and resistance training in treating sarcopenia. Limitations: Limited eligible reviews restricted synthesis and interpretation of findings. Conclusion and implications of key findings: There is a lack of high quality research with which to inform the treatment of sarcopenia with exercise. Further research using more precision when selecting sarcopenic populations and outcomes is required in this field. This will enable the identification of effective ways of treating sarcopenia with exercise before evidence-based clinical guidelines can be established.